Rapid turnover of acetyl groups in the four core histones of simian virus 40 minichromosomes. - Chestier, A (1979)
The four core histones (H2a, H2b, H3, and H4) bound to simian virus 40 minichromosomes isolated from infected cells contain rapidly labeled acetyl groups in internal positions of the histone polypeptide chain. Upon chase, these acetyl residues decay with a half-life of less than 15 min. The acetyl groups are incorporated in histones bound to mature chromosomes and not in newly synthesized histones bound to replicating viral chromosomes. The rate of acetate incorporation is not related to the degree of steady state acetylation of the individual viral or cellular histones. This rate is 4-fold higher for the viral chromatin than for its cellular counterpart isolated from the same nuclei. The possible role for histone acetylation in viral genome expression is discussed.